Pola Ritmik Tifa pada Tari Cakalele - Giovan, Jeremy (Program Studi Pendidikan Musik, 2023)
The Aim of Study was to find out the rhythmic pattern of tifa in Cakalele Dance and to write the rhythmic patterns’ notation and to document in the form of scientific papers. The Research Method used to compile this research is the descriptive qualitative research method which explains the research object based on interview results, literature study, and video observation. This research was conducted on July 2018 until January 2020 in Jakarta and Bogor. The Study Result proves that the rhythmic pattern of tifa in Cakalele Dance has a very important role to organize the show course where tifa is the main instrument and the most important compared to the other instruments. There is one basic rhythmic pattern as a guide to accompany The Cakalele Dance, but as time goes along with human’s creativity then new rhythmic patterns were created as the variation of the basic rhythmic pattern itself. The rhythmic pattern of tifa in accompanying The Cakalele Dance tend to be constant and stabile, so there will not be any changes of rhythmic pattern during the show. The probability of rhythmic pattern change will only happen if there is a pause in the show course. The Implication of this research is the documentation of the rhythmic patterns’ notation of tifa which adjusted according to the hit shape as a learning and preservation source for general public especially artists and academicians who wanted to learn about the knowledge.